Strategi Agensi Humas PT. United Communications dalam Membina Hubungan Baik dengan Media - Misyelia; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Many companies are having trouble in maintaining relations with the media. Therefore, one of the relationships with the press is the PR consultant service to run the company's locale program. The goal of this study is to identify and understand strategies for building good relationships with the media implemented by the United Communications company. This study uses constructivist paradigm, a qualitative approach, a type of descriptive research with a case study method. Data collection techniques are obtained through in-depth interviews, participant observations, and document research. This research show that United communications are successfully enough to build good relationships with media. The strategy by PT. United Communications, namely determining the programs and targets of PR programs, implementing programs that have been made, and producing publications through the media. After that, the last stage carried out by PT. United Communications is evaluating media relations based on the KPI and the obje ctives from each client.